Druga rocznica Powstania Warszawskiego. (Elbląg : [s.n.], 1946)
Afisz inf. o obchodach rocznicowych.
Keywords: Warszawa (Polska) -- 1944 (Powstanie Warszawskie) -- rocznice; Elbląg (Polska) -- 1945-1970 -- druki ulotne; Elbląg (Polska) -- 1945-1970 -- źródła